The Effectiveness of Diabetic Foot Care (DiFoCa) on the Foot Care Behavior of Diabetes Mellitus Patients : A Quasi-Experimental Study with a Control Group - Imamah, Ida Nur; Dwi Prajayanti, Eska; Margatot, Didik Iman (Universitas Muhammadiyah Surakarta, 2026)
Diabetes Mellitus (DM) is the second most common disease in Indonesia after hypertension. Diabetes Mellitus can cause complications, one of which is diabetic ulcer. Diabetic ulcer can lead to amputation of the extremities, especially the lower extremities. Prevention measures that can be taken to prevent diabetic ulcer include foot care therapy. Foot care consists of three preventive measures, starting with education on foot care, diabetic foot exercises, and management of foot injuries/wounds. Foot care training was conducted for five weeks. The study aimed to determine the effect of Diabetes Foot Care Training on the foot care behavior of D patients. Foot care behavior was assessed using the Nottingham Assessment of Functional Footcare (NAFF) tool. The research was conducted over 5 weeks. The study involved 60 respondents divided into an intervention group and control group. The results of the control group showed a p-value > 0,005 (0,647), indicating no difference in foot care behavior in the control group. The Wilcoxon test for the intervention group showed a p-value < 0,005 (0,002), indicating a difference in foot care behavior before and after the intervention. The Mann Whitney test showed a p-value < 0,005 (0,027). The conclusion of the study states that Difoca intervention has an effect on improving foot care behavior in DM patients.